The Evolution of Auguste Comte on the Tradition of Rejecting Bala Mappanre Tau Lotong in Lallatang Village, Dua Boccoe Sub-District, Bone Regency - Desi; Musafir Pabbabari; Indo Santalia (Jurnal Mercusuar, 2023)
This research discusses evolution Auguste Comte’s or three-stage law interacts with the tradition of "tolak bala mappanre tau lotong" in the village of Lallatang, Dua Boccoe District, Bone Regency. This type of research is classified as qualitative descriptive research, utilizing the following research approaches: Historical approach, anthropological approach, religious approach, and anthropological approach. The data sources for this research include traditional leaders, several community figures, and relevant literature. The data collection methods employed are literature review, observation, interviews, and documentation. The data processing and analysis involve three stages: data reduction, data presentation, and drawing conclusions. The results of this research indicate that the tradition of "tolak bala mappanre tau lotong" with its linear pattern aligns with the three-stage law. Human development in the theological stage explains that humans seek the first principle or primary cause of all events, linking phenomena to the supernatural or metaphysical forces, whether originating from nature, objects, humans, or beyond.